Effects of Carbonization Parameters of Moso-Bamboo-Based Porous Charcoal on Capturing Carbon Dioxide - Pei-Hsing Huang; Jhih-Wei Jhan; Yi-Ming Cheng; Hau-Hsein Cheng (The Scientific World Journal)
This study experimentally analyzed the carbon dioxide adsorption capacity of Moso-bamboo- (Phyllostachys edulis-) based porous charcoal. The porous charcoal was prepared at various carbonization temperatures and ground into powders with 60, 100, and 170 meshes, respectively. In order to understand the adsorption characteristics of porous charcoal, its fundamental properties, namely, charcoal yield, ash content, pH value, Brunauer-Emmett-Teller (BET) surface area, iodine number, pore volume, and powder size, were analyzed. The results show that when the carbonization temperature was increased, the charcoal yield decreased and the pH value increased. Moreover, the bamboo carbonized at a temperature of 1000°C for 2 h had the highest iodine sorption value and BET surface area. In the experiments, charcoal powders prepared at various carbonization temperatures were used to adsorb 1.854% CO2 for 120 h. The results show that the bamboo charcoal carbonized at 1000°C and ground with a 170 mesh had the best adsorption capacity, significantly decreasing the CO2 concentration to 0.836%. At room temperature and atmospheric pressure, the Moso-bamboo-based porous charcoal exhibited much better CO2 adsorption capacity compared to that of commercially available 350-mesh activated carbon.